Salt affected soils in Jammu and Kashmir: Their management for enhancing productivity - GUPTA, R. D.; ARORA, SANJAY (Journal of Soil and Water Conservation, 2020)
Saline soils in valley of Kashmir and Kandi belt of Jammu have been reported, having soluble salts in the range of 0.15 to 0.45% with Cl, NO3, SO4 and HCO3 anions. Saline soils have been reported in many soils of Jammu district derived from alluvium parent material in the plains as well as in soils of Parmandal and Uttar bani areas which are their origin to Siwalik group of rocks. Presence of soluble salts greater than 0.2% was found harmful to plants. In the canal command area, located in the Kathua and Jammu districts it was found that an area of 25,670 ha become unproductive due to salinization alkalization as well as waterlogging. The soils are very strongly alkaline having pH range from 8.6 to 10.5 (average pH 9.9), with dominance of exchangeable Na (ESP 25.3) and sodium adsorption ratio (SAR) of 78.41. The highest ESP was recorded in Tarore soil with ustic and aquic moisture regimes associated with hard surface crust, calcic and natric sub-surface horizons. Gypsum requirement (GR) to amend sodic soil was calculated and applied at the rate of 100% GR. This application has increased rice and wheat yields 43.3 and 86.9%, respectively, over control. Improvement in soil properties was noticed, soil pH decreased from 9.7 to 8.8, bulk density decreased from 1.52 to 1.48 Mg m-3 and infiltration rate was improved.